2006
DOI: 10.1002/gps.1545
|View full text |Cite
|
Sign up to set email alerts
|

Personality and behaviour changes mark the early stages of Alzheimer's disease in adults with Down's syndrome: findings from a prospective population-based study

Abstract: These findings confirm that the early presentation of AD in DS is characterized by prominent personality and behaviour changes, associated with executive dysfunction, providing support for the notion that the functions of the frontal lobes may be compromised early in the course of the disease in this population. This has important implications for the diagnosis, treatment and management of dementia in people with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 51 publications
(62 reference statements)
5
148
0
7
Order By: Relevance
“…In particular, behavioral changes such as withdrawal and apathy appear to be early signs of dementia and are typically observed by caretakers prior to the onset of measurable cognitive changes or declines [Alwyard et al, 1997;Holland et al, 2000]. Following 55 adults over a 5 year period, Ball et al [2006] found that, unlike the general population, behavioral and personality changes as opposed to memory changes are prominent in the early, preclinical stages of dementia in Down syndrome. This pattern supports the hypothesis that frontal lobe dysfunction and dementia of the frontal type, may be characteristic of the early course or manifestation of Alzheimer's disease in Down syndrome [see Holland et al, 2000].…”
Section: Adultsmentioning
confidence: 98%
“…In particular, behavioral changes such as withdrawal and apathy appear to be early signs of dementia and are typically observed by caretakers prior to the onset of measurable cognitive changes or declines [Alwyard et al, 1997;Holland et al, 2000]. Following 55 adults over a 5 year period, Ball et al [2006] found that, unlike the general population, behavioral and personality changes as opposed to memory changes are prominent in the early, preclinical stages of dementia in Down syndrome. This pattern supports the hypothesis that frontal lobe dysfunction and dementia of the frontal type, may be characteristic of the early course or manifestation of Alzheimer's disease in Down syndrome [see Holland et al, 2000].…”
Section: Adultsmentioning
confidence: 98%
“…The results of cross-sectional and longitudinal studies suggest that changes in the personality and behavior of adults with DS can indicate the early stages of dementia prior or simultaneous to the onset of other typical AD symptoms such as cognitive decline [19,20,21,22,23]. Those initial alterations are comparable to the changes associated with frontotemporal dementia in the general population and are considered precursors of the development of AD in individuals with DS, indicating that the frontal and temporal lobes are the brain regions first affected in this population [23,24,25]. In fact, in the brains of individuals with DS, the deposition of Aβ initially occurs in the frontal and entorhinal cortices, subsequently spreading to other brain regions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Para ello, es muy importante el reconocimiento de los primeros signos de la EA en la persona con SD que, en muchas ocasiones, pueden traducirse como cambios en la personalidad y en el comportamiento, ya que pueden ser la clave para una intervención temprana y un mejor pronóstico de la enfermedad (Ball et al, 2006).…”
Section: Discussionunclassified
“…Aunque no existe un amplio consenso, los problemas en la memoria episódica podrían no ser los primeros síntomas (Nieuwenhuis-Mark, 2009) sino que suelen ser más comunes otros síntomas más relacionados con limitaciones en el funcionamiento del lóbulo frontal, tales como indiferencia, falta de cooperación, apatía, depresión, comunicación social deficiente o dificultades en conducta adaptativa (Ball et al, 2006;Key y Dykens, 2014).…”
Section: Introductionunclassified